ANALISIS KETIDAKADILAN GENDER NOVEL TERJEMAHAN PACHINKO KARYA MIN JIN LEE SERTA PEMANFAATANNYA SEBAGAI INVENSI PENYUSUNAN BAHAN AJAR PENULISAN RESENSI NOVEL DI SMK - Ivana Magdalena; Raheni Suhita (Universitas Batanghari, 2025)
This study aims to describe and explain the forms of gender injustice experienced by female characters in the translated novel Pachinko and the use of research results as an invention for compiling teaching materials for writing novel reviews in vocational high schools. This research is a qualitative descriptive study with a content analysis approach. The data sources for this study are document sources in the form of the translated novel Pachinko and informants, namely two Indonesian language teachers and five grade XII students of SMK Warga Surakarta. The sampling technique used purposive sampling technique. Data collection was carried out by document analysis and in-depth interviews with informants directly. The validation technique used the theory triangulation technique and data source triangulation. The results of this study indicate that the forms of gender injustice in the translated novel Pachinko by Min Jin Lee are described as a reflection of the reality of social inequality and discrimination that women often experience. This injustice is reflected in five forms, namely marginalization, subordination, stereotypes, violence, and double workloads dominated by acts of violence including economic, sexual, physical, and verbal violence; and according to the teacher's perception, the results of the analysis of the Pachinko novel can be used as teaching materials for writing novel reviews for grade XII in vocational high schools.